The death cure eaudiobook - Dashner, James (Maze Runner, 2011)
THE #1 NEW YORK TIMES BESTSELLING MAZE RUNNER SERIES • “[A] mysterious survival saga that passionate fans describe as a fusion of Lord of the Flies [and] The Hunger Games ” ( Entertainment Weekly ) WICKED has taken everything from Thomas: his life, his memories, and now his only friends—the Gladers. But it’s finally over. The trials are complete, after one final test. What WICKED doesn’t know is that Thomas remembers far more than they think. And it’s enough to prove that he can’t believe a word of what they say. Thomas beat the Maze. He survived the Scorch. He’ll risk anything to save his friends. But the truth might be what ends it all. The time for lies is over. The first two books, The Maze Runner and The Scorch Trials , are also #1 worldwide blockbuster movies featuring the star of MTV's Teen Wolf , Dylan O'Brien; Kaya Scodelario; Aml Ameen; Will Poulter; and Thomas Brodie-Sangster! Look for more books in the blockbuster Maze Runner series: THE MAZE RUNNER • THE SCORCH TRIALS • THE DEATH CURE • THE KILL ORDER • THE FEVER CODE